2007
DOI: 10.1158/1055-9965.epi-06-0743
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Bladder Cancer Associated with Family History of Cancer: Do Low-Penetrance Polymorphisms Account for the Increase in Risk?

Abstract: The relationship between family history of cancer in firstdegree relatives and risk of bladder cancer was examined in the Spanish Bladder Cancer Study. Information on family history of cancer was obtained for 1,158 newly diagnosed bladder cancer cases and 1,244 controls included in 18 hospitals between 1998 and 2001. A total of 464 (40.1%) cases and 436 (35.1%) controls reported a family history of cancer in z1 relative [odds ratio (OR), 1.32; 95% confidence interval (95% CI), 1.11-1.59]; the OR was 1.23 (95% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
66
2
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 48 publications
8
66
2
5
Order By: Relevance
“…39 Such data support the concept of low-penetrance cancer-predisposing polymorphisms acting together and/or interacting with environmental factors, to increase the familial risk of bladder cancer. 40 However, the familial risk of bladder cancer is not well understood and, to date, little attention has been paid to the joint effect of smoking and family history in modifying the risk of bladder cancer, in part because of the limitations of case control studies. This limitation was overcome in a family-based population analysis of incident bladder cancer, in which probands who had smoked and who also had a positive family history were at 5.31-fold increased risk of bladder cancer.…”
Section: Bladder Cancer Carcinogenesismentioning
confidence: 99%
“…39 Such data support the concept of low-penetrance cancer-predisposing polymorphisms acting together and/or interacting with environmental factors, to increase the familial risk of bladder cancer. 40 However, the familial risk of bladder cancer is not well understood and, to date, little attention has been paid to the joint effect of smoking and family history in modifying the risk of bladder cancer, in part because of the limitations of case control studies. This limitation was overcome in a family-based population analysis of incident bladder cancer, in which probands who had smoked and who also had a positive family history were at 5.31-fold increased risk of bladder cancer.…”
Section: Bladder Cancer Carcinogenesismentioning
confidence: 99%
“…Table 4 summarizes pertinent details of 9 case-control and 4 cohort studies in which family history of TCCUT was quantitatively evaluated as a bladder cancer risk factor. [12][13][14][15][16][17][18][19][20][21][22][23][24] These studies varied widely in sample size, quality of design and analysis, inclusion/exclusion of upper urinary tract sites, and the extent to which reported cancers were objectively documented, but are surprisingly similar in their estimated risk ratios. These range from 1.2 to 6.1 among male and female cases combined, with most of the results clustering between 1.4 and 1.9.…”
Section: Case Reports Of Familial Tccutmentioning
confidence: 99%
“…[2,7] Common variants in low-penetrance genes involved in the metabolism of environmental toxins have been shown to modify individual susceptibility to bladder carcinogens. [2] Furthermore, a genetic predisposition to bladder cancer is suggested by the occurrence of TCCUT in several Mendelian disorders [8][9][10][11], epidemiologic studies showing that a positive TCCUT family history increases bladder cancer risk [12][13][14][15][16][17][18][19][20][21][22][23][24], and a limited number of case reports describing multiple-case TCCUT families. [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] Therefore, both genetic and environmental factors play a role in the development of bladder and related urinary tract cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Another large caseÁcontrol study from Spain among 1158 bladder cancer cases and 1244 controls found an increased risk of bladder cancer by a factor of 2.34 (95% CI 0.95Á5.77) for those reporting a positive family history of bladder cancer [12] Goldgar et al [13] estimated O/E ratios in the Utah Population Database by identifying all cases of cancer in first degree relatives of patients. The first degree relatives of bladder cancer probands were found to have an increased risk of bladder cancer of 1.5 (95% CI 1.0Á2.2) (not adjusted for smoking).…”
Section: Epidemiological Evidencementioning
confidence: 99%